MANAGEMENT STRATEGIES FOR ENCOURAGING MALE ENROLMENT IN SECONDARY SCHOOLS IN ANAMBRA STATE - Akudo, Florence Ukamaka (UNIZIK Journal of Educational Management and Policy, 2024)
The study examined management strategies for encouraging male enrolment in secondary schools in Anambra State. The study adopted the descriptive survey design. The population of the study consisted of boys and co-educational secondary school principals, teachers and dropouts from the markets, motor parks and mechanic workshops in Anambra State. In all, 894 respondents were used for the study. The instrument for data collection was a questionnaire that comprised two sections A and B. The instrument was structured on a four-point rating scale of Strongly Agree, Agree, Disagree and Strongly Disagree. The reliability of the instrument was determined using Cronbach Alpha Reliability Co-efficient. The instrument was administered on 20 respondents (2 principals, 8 teachers and 10 dropouts in the market, mechanic workshops and motor parks) from Enugu State with the help of 2 trained research assistants. A reliability co-efficient of 0.73 was obtained and indicated appropriate for the study. Mean and Analysis of Variance (ANOVA) were used for data analyses. The study revealed that psychological strategies and administrative strategies are identified strategies for encouraging male enrolment in secondary schools in Anambra State. Based on the findings and conclusion, the study recommended that Schools should embrace a holistic approach by integrating diverse psychological strategies, such as teaching technical skills, providing counseling, and fostering engaging activities, to create an environment conducive for male students’ enrollment in secondary schools